Effect of cantilever length on stress distribution around implants in mandibular overdentures supported by two and three implants - Ebadian, Behnaz; Mosharraf, Ramin; Khodaeian, Niloufar (European Journal of Dentistry, 2016)
Objective: There is no definitive study comparing stress distribution around two versus three implants in implant-retained overdentures with different cantilever length. The purpose of this finite element study was to evaluate stress pattern around the implants of the 2 or 3 implant-supported mandibular overdenture with different cantilevered length. Materials and Methods: The models used in this study were 2 and 3 implant-supported overdenture with bar and clip attachment system on an edentulous mandibular arch. Each model was modified according to cantilever length (0 mm, 7 mm, and 13 mm); thus, 6 models were obtained. The vertical load of 15 and 30 pounds were applied unilaterally to the first molar and 15 pounds to the first premolar, and the stress in bone was analyzed. Results: With increasing cantilever length, no similar stress pattern changes were observed in different areas, but in most instances, an increase in cantilever length did not increase the stress around the implant adjacent to cantilever. Conclusions: Within the limitations of this study, it can be concluded that increasing of cantilever length in mandibular overdentures retained by 2–3 implants did not cause distinct increasing in stress, especially around the implant adjacent to cantilever, it may be helpful to use cantilever in cases of mandibular overdenture supported by splinted implants with insufficient retention and stability. Based on the findings of this study, optimal cantilever length in mandibular overdenture cannot be determined.
Keywords: Cantilever; finite element analysis; overdenture; stress